Public Service Model Development Strategy the Quality in the Sub-Districts in The Government of The Sidoarjo Regency - Lukman Arif; Diana Hartati (Future Science)
The image of government services is still considered unsatisfactory to the public. Various complaints from the implementation of services continue to color the world of public services in Indonesia. Reluctance and negative image in the service process faced by the community is still felt when they have to deal with government agencies in a service. This shows an indication that the government has yet to succeed in providing quality and satisfying services to the community. This research is part of an effort to make continuous improvements in service quality. The objectives of this study are 1) to identify the quality of public service delivery in the sub-districts of the Sidoarjo Regency Government, 2) to identify the role of the local government in providing quality public services in the sub-districts of the Sidoarjo Regency Government. This research method uses a descriptive qualitative approach; by presenting the results of this study in depth about the phenomenon of public service in improving the quality of service in the sub-districts in the Sidoarjo Regency Government. The results showed that the implementation of public services in the sub-districts in the Sidoarjo Regency Government environment is relatively good enough. The role of the Sidoarjo Regency Government focuses more on the position as facilitator, dynamist and executor within the existing normative boundaries.